The Russia–Ukraine War and the Struggle to Shape the New International Order - Tarhini, Kamal Kamel (Journal of Economic, Administrative and Legal Sciences, 2025)
This study examines the Russia–Ukraine war as a pivotal moment in the transformation of the international system, exploring the nature of the conflict and its geopolitical, economic, and technological dimensions, along with its impact on global power dynamics. The significance of the study lies in its contribution to understanding the current transitional phase of the international order, demonstrating how the war has become a formative factor in reshaping international relations and future geopolitical balances, and offering an analytical reference for interpreting ongoing shifts and anticipating what may follow. The study adopts an analytical–inductive methodology based on reviewing relevant literature, strategic documents, and historical and political trajectories preceding and following the war, in addition to assessing potential future scenarios. The findings reveal that the war exposed the limits of U.S. hegemony and triggered a tangible shift toward an emerging multipolar order, reflected in the rising influence of Russia, China, and India, and the growing relevance of groupings such as BRICS and the Shanghai Cooperation Organization. They also highlight the increasing centrality of economic and technological competition and the declining effectiveness of traditional international institutions in crisis management.
Keywords: Russia–Ukraine war; international system; multipolarity; balance of power; geopolitics; BRICS; international institutions; geotechnology